2014
DOI: 10.1152/ajpregu.00028.2014
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomy eliminates the maximal cardiac output response to six weeks of exercise training

Abstract: With this study we tested the hypothesis that 6 wk of endurance training increases maximal cardiac output (Qmax) relatively more by elevating blood volume (BV) than by inducing structural and functional changes within the heart. Nine healthy but untrained volunteers (Vo2max 47 ± 5 ml·min(-1)·kg(-1)) underwent supervised training (60 min; 4 times weekly at 65% Vo2max for 6 wk), and Qmax was determined by inert gas rebreathing during cycle ergometer exercise before and after the training period. After the traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
6
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 57 publications
6
97
6
2
Order By: Relevance
“…A recent paper documented a 7% (P Ͻ 0.05) increase in BV accompanied with a 10% (P Ͻ 0.05) increased V O 2peak following 6 wk of endurance training (5). The investigators then removed, via phlebotomy, the training-induced BV and observed V O 2peak returned to a level not differing from pretraining values.…”
Section: Discussionmentioning
confidence: 96%
“…A recent paper documented a 7% (P Ͻ 0.05) increase in BV accompanied with a 10% (P Ͻ 0.05) increased V O 2peak following 6 wk of endurance training (5). The investigators then removed, via phlebotomy, the training-induced BV and observed V O 2peak returned to a level not differing from pretraining values.…”
Section: Discussionmentioning
confidence: 96%
“…Studies employing acute expansion of blood volume by intravenous infusion of dextran (198,236) or albumin (115) have demonstrated that increased blood volume significantly influences cardiac performance by increasing cardiac preload, ventricular filling and stroke volume. Reestablishing blood volume to a level similar to that observed before a 6-week training intervention by phlebotomy, abolished the training-induced change in maximal cardiac output, suggesting that the training-induced change in maximal cardiac output following a short period of exercise training is a consequence of an increase in blood volume (39). Furthermore, a large part of the difference in stroke volume between trained and untrained has also been suggested to be related to differences in blood volume (198,236).…”
Section: Blood Volume Response To Exercise Trainingmentioning
confidence: 89%
“…relaxes quickly and fills to a large end-diastolic volume, but a decreased vascular resistance could also contribute (54). In healthy volunteers, the initial (6 wk) exercise training-induced increase in SV seems to be the product of increased blood volume rather than structural changes within the myocardium (9). Remarkably, 1 yr of exercise training in previously untrained individuals induced morphological adaptations similar to those observed in athletes, including augmented LV mass from 168 Ϯ 38 to 203 Ϯ 46 g; surprisingly, this did not alter Q max as much as could have been expected (from 20.1 Ϯ 5.1 to 21.9 Ϯ 5.4 l/min) since Starling and pressure/volume curves approached but did not match those of elite athletes (3).…”
Section: How and By How Muchmentioning
confidence: 99%